Trace element alterations before and after cardiopulmonary bypass in patients undergoing coronary artery bypass grafting - (:unkn) unknown (DUSTRI-VERLAG DR KARL FEISTLE, 2001)
Trace elements (TE) are known to play a key role in myocardial metabolism. In this study, the serum levels of zinc (Zn) and copper (Cu) were determined in 15 consecutive patients with coronary artery disease admitted for coronary artery bypass grafting. To analyze the trace elements, blood samples were drawn into metal-free tubes just prior to the start of cardiopulmonary bypass; within the first 30 min of cardiopulmonary bypass; 30 min following cardiopulmonary bypass; first postoperative day; 2nd postoperative day and 3rd postoperative day. Trace element analyses were performed using atomic absorption spectrophotometry. Mean age was 53.1 +/- 8.7 years and 87% were men. Mean cardiopulmonary bypass time was 80.8 +/- 18.1 min. The preoperative serum concentrations of zinc were normal. There were remarkable decreases in serum levels of Cu and Zn on the second postoperative day in all patients compared to the preoperative levels of Cu and Zn. On the first postoperative day, mean levels of zinc were decreased and a gradual rise followed on the third day. All patients had serum zinc above the lower limit of normal range. These data indicate that severe loss of various trace elements might occur in patients undergoing cardio pulmonary bypass.
Keywords: zinc; copper; coronary artery bypass; COPPER; HEART; ZINC; INTERLEUKIN-1; SELENIUM; SURGERY; BINDING; SERUM; IRON